1998
DOI: 10.1007/s002689900381
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Colorectal Liver Metastases: 25‐Year Experience

Abstract: The aim of this retrospective study was to analyze survival and prognostic factors in 111 consecutive patients undergoing curative resection of liver metastases from colorectal cancer. In addition, the time periods 1971-1984 and 1985-1995 were compared; criteria for first liver resection did not change with time, whereas the attitude toward re-resection was more aggressive during the latter period. Operative mortality was 6% during 1971-1984 and 0% during 1985-1995 (3.6% for all patients). The crude 5-year act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
137
0
19

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(161 citation statements)
references
References 26 publications
5
137
0
19
Order By: Relevance
“…The intrahepatic tumour number as an exclusion criterion for liver surgery is still a matter of debate. Several investigators regard three tumours as an upper limit when liver resection is to be performed (61,62,64,66), while in other studies the tumour number has not been found to be a significant prognostic factor (59,60,63,65,67). It is estimated that 10 Á/20% of all patients with colorectal liver metastases are candidates for liver surgery (76).…”
Section: Resection Of Recurrencementioning
confidence: 99%
See 2 more Smart Citations
“…The intrahepatic tumour number as an exclusion criterion for liver surgery is still a matter of debate. Several investigators regard three tumours as an upper limit when liver resection is to be performed (61,62,64,66), while in other studies the tumour number has not been found to be a significant prognostic factor (59,60,63,65,67). It is estimated that 10 Á/20% of all patients with colorectal liver metastases are candidates for liver surgery (76).…”
Section: Resection Of Recurrencementioning
confidence: 99%
“…A careful and individual evaluation of (67,74), and also series with simultaneous resection of hepatic and extrahepatic metastases have demonstrated 5-year survival rates approaching 30% (45,75). The intrahepatic tumour number as an exclusion criterion for liver surgery is still a matter of debate.…”
Section: Resection Of Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies comparing metastases with and without desmoplastic encapsulation have reported a positive impact on survival of desmoplasia per se. [7][8][9][10][11][12][13] In consequence, the aim of the present study was in a population treated according to modern guidelines and indications to examine the prognostic value of the histological growth patterns for survival.…”
mentioning
confidence: 99%
“…27 They demonstrated that five factors were independently significant: grade of liver tumor, extra hepatic metastases, intra-operative blood transfusion and the preoperative CEA level and whether the operation was performed in the earlier 15-year period versus the later 5-year period. They reported that when there are extra-hepatic metastases, satelitosis, poorly differentiated liver metastases or positive resection margins none of the patients survived for 5 years.…”
Section: Prognostic Evaluation Patient Selection and Recent Advancesmentioning
confidence: 99%